为了澄清其他人提到的内容,请考虑以下类型的非空列表:
data NonEmptyList a = One a | Many a (NonEmptyList a)
map :: (a -> b) -> NonEmptyList a -> NonEmptyList b
map f (One x) = One (f x)
map f (Many x xs) = Many (f x) (map f xs)
(++) :: NonEmptyList a -> NonEmptyList a -> NonEmptyList a
One x ++ ys = Many x ys
Many x xs ++ ys = Many x (xs ++ ys)
tails :: NonEmptyList a -> NonEmptyList (NonEmptyList a)
tails l@(One _) = One l
tails l@(Many _ xs) = Many l (tails xs)
您可以编写一个有效的comonad实例,如下所示:
instance Functor NonEmptyList where
fmap = map
instance Comonad NonEmptyList where
coreturn (One x) = x
coreturn (Many x xs) = x
cojoin = tails
-- this should be a default implementation
x =>> f = fmap f (cojoin x)
让我们证明哈马尔列出的定律。作为给定的第一步,我将冒昧地对每一个进行 eta 扩展。
法 1。
(coreturn . cojoin) xs = id xs
-- definition of `.`, `cojoin`, and `id`
(coreturn (tails xs) = xs
-- case on xs
-- assume xs is (One x)
(coreturn (tails (One x))) = One x
-- definition of tails
(coreturn (One (One x))) = One x
-- definition of coreturn
One x = One x
-- assume xs is (Many y ys)
(coreturn (tails (Many y ys))) = Many y ys
-- definition of tails
(coreturn (Many (Many y ys) (tails ys)) = Many y ys
-- definition of coreturn
Many y ys = Many y ys
-- assume xs is _|_
(coreturn (tails _|_)) = _|_
-- tails pattern matches on its argument
(coreturn _|_) = _|_
-- coreturn pattern matches on its argument
_|_ = _|_
法 2。
(fmap coreturn . cojoin) xs = id xs
-- definition of `.`, `cojoin`, `fmap`, and `id`
map coreturn (tails xs) = xs
-- case on xs
-- assume xs is (One x)
map coreturn (tails (One x)) = One x
-- defn of tails
map coreturn (One (One x)) = One x
-- defn of map
One (coreturn (One x)) = One x
-- defn of coreturn
One x = One x
-- assume xs is (Many y ys)
map coreturn (tails (Many y ys)) = Many y ys
-- defn of tails
map coreturn (Many (Many y ys) (tails ys)) = Many y ys
-- defn of map
Many (coreturn (Many y ys)) (map coreturn (tails ys)) = Many y ys
-- defn of coreturn
Many y (map coreturn (tail ys)) = Many y ys
-- eliminate matching portions
map coreturn (tail ys) = ys
-- wave hands.
-- If the list is not self-referential,
-- then this can be alleviated by an inductive hypothesis.
-- If not, then you can probably prove it anyways.
-- assume xs = _|_
map coreturn (tails _|_) = _|_
-- tails matches on its argument
map coreturn _|_ = _|_
-- map matches on its second argument
_|_ = _|_
法 3。
(cojoin . cojoin) xs = (fmap cojoin . cojoin) xs
-- defn of `.`, `fmap`, and `cojoin`
tails (tails xs) = map tails (tails xs)
-- case on xs
-- assume xs = One x
tails (tails (One x)) = map tails (tails (One x))
-- defn of tails, both sides
tails (One (One x)) = map tails (One (One x))
-- defn of map
tails (One (One x)) = One (tails (One x))
-- defn of tails, both sides
One (One (One x)) = One (One (One x))
-- assume xs = Many y ys
(this gets ugly. left as exercise to reader)
-- assume xs = _|_
tails (tails _|_) = map tails (tails _|_)
-- tails matches on its argument
tails _|_ = map tails _|_
-- tails matches on its argument, map matches on its second argument
_|_ = _|_